PENGARUH RASIO LIKUIDITAS, RASIO PROFITABILITAS, RASIO SOLVABILITAS, RASIO AKTIVITAS DAN RASIO PASAR TERHADAP HARGA SAHAM - Mayang Oktaviani Malik; Yuliusman Yuliusman; Susfa Yetti (Jurnal Manajemen Terapan dan Keuangan, 2023)
The purpose of this study was to determine the effect of liquidity ratios, profitability ratios, solvency ratios, activity ratios, and market to share price ratios in companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange for the 2019-2021 period. The samples in this study were 39 Companies in the Basic Industry and Chemical Sector Listed on the Indonesian Stock Exchange. The data in this research is secondary data. The analytical method used is the classical assumption test and multiple regression analysis using the SPSS 25 program. The results show that simultaneously the variable liquidity ratios, profitability ratios, solvency ratios, activity ratios, and market ratios affect stock prices. Partially, market ratios have an effect on stock prices, while liquidity ratios, profitability ratios, solvency ratios, and activity ratios have no effect on stock prices in chemical and basic industrial companies listed on the Indonesia Stock Exchange in 2019-2021.